2021
DOI: 10.3389/fcimb.2021.723840
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota and Fecal Metabolites Associated With Neurocognitive Impairment in HIV-Infected Population

Abstract: Gut microbiota dysbiosis has been associated with many neurological diseases. However, how microbiota composition and metabolism relate to neurocognitive impairment (NCI) in HIV-infected individuals is largely unknown. In this study, a total of 102 HIV infected participants were classified into two groups—those with NCI and those without—using the global deficit score (GDS). Fecal samples were collected from the participants for 16S rRNA gene sequencing and untargeted metabolomics. The plasma level of 25 hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 38 publications
(51 reference statements)
0
19
0
Order By: Relevance
“…The same group also performed 16S rRNA gene sequencing and untargeted metabolomics on fecal samples of PLWH with or without neurocognitive impairment (NCI). The results show that the decreased abundance of butyrate-producing bacteria, the increased abundance of Klebsiella, and the associated metabolites were associated with NCI in PLWH ( 65 ).…”
Section: Systems Epidemiology Of Hiv/aidsmentioning
confidence: 91%
See 2 more Smart Citations
“…The same group also performed 16S rRNA gene sequencing and untargeted metabolomics on fecal samples of PLWH with or without neurocognitive impairment (NCI). The results show that the decreased abundance of butyrate-producing bacteria, the increased abundance of Klebsiella, and the associated metabolites were associated with NCI in PLWH ( 65 ).…”
Section: Systems Epidemiology Of Hiv/aidsmentioning
confidence: 91%
“…Very recently, Ding et al conducted a case-control study using untargeted metabolomics to characterize the key metabolites and metabolic pathways associated with HIV infection and multiple NCDs, focusing on identifying the common metabolic pathways underlying them (64). They found that PLWH presented widespread alterations in cellular metabolism versus HIV-negative individuals, and glycerophospholipid metabolism emerged as the potential common metabolic pathway underlying NCDs in treated HIV infection; followed by d-glutamine and d-glutamate, and alanine, aspartate and glutamate metabolism.…”
Section: Systems Epidemiology Of Hiv/aidsmentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24] However, previous studies mainly focused on comparing the gut microbiota between HIVinfected and HIV-uninfected heterosexual individuals and have not considered the immunologic response among PLHIV on ART. [25][26][27][28] In many settings, men who have sex with men (MSM) account for the majority of HIV/AIDS cases. 29 However, the role of microbiota in immune reconstitution for HIV-infected MSM is still understudied.…”
Section: Introductionmentioning
confidence: 99%
“…Gut microbiota plays an important role in maintaining the host’s health, and many researchers pay attention to the cross talk between the gut and brain ( Han et al., 2020 ; Qiao et al., 2020 ; Kovács et al., 2021 ; Khoshkam et al., 2021 ). Mounting evidence shows that gut microbiota can affect the host’s brain functions and behaviors via the “microbiota–gut–brain” axis ( Chen et al., 2021 ; Rajput et al., 2021 ; Ding et al., 2021 ; Dong et al., 2021 ). In our previous work, we found significant differences in gut microbiota compositions between MDD patients and healthy controls (HC) ( Chen et al., 2020 ; Bai et al., 2021 ), and these differences were specifically relative to bipolar disorder and schizophrenia ( Zheng et al., 2019 ; Zheng et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%